Evidence-Based Review: Efektivitas Effleurage Massage dalam Proses Persalinan - Ni Kadek Ayu Sriani; Ni Made Dwi Mahayati; Ni Nyoman Budiani (JURNAL WACANA KESEHATAN, 2026)
Labor is a physiological process commonly accompanied by pain, particularly during the active phase of the first stage of labor. Poorly managed labor pain may increase anxiety, tension, and negatively affect the progress of labor. One of the non-pharmacological methods that can be used to reduce labor pain is effleurage massage. This study aimed to review scientific evidence regarding the effectiveness of effleurage massage during labor. The study employed an evidence-based review design using a systematic literature review approach. Article searches were conducted through PubMed/PMC, Cochrane Library, ScienceDirect, and Google Scholar databases for publications from 2020–2026 using keywords related to effleurage massage and labor. Based on the selection process according to the inclusion and exclusion criteria, 12 articles were included for further analysis. The findings showed that most studies reported that effleurage massage was effective in reducing labor pain intensity during the active phase of the first stage of labor, decreasing maternal anxiety, improving relaxation and comfort, and shortening labor duration. The effectiveness of effleurage massage is associated with tactile stimulation mechanisms based on the gate control theory and endorphin release, which help inhibit pain impulse transmission. In conclusion, effleurage massage is a safe, easy-to-apply, and effective non-pharmacological intervention to support a more comfortable and humanized childbirth process.